2014
DOI: 10.1039/c4ra08503e
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial properties of light-activated polydimethylsiloxane containing crystal violet

Abstract: Crystal violet was incorporated into polydimethylsiloxane (PDMS) by a swell–encapsulation–shrink method using chloroform as a swelling solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 21 publications
4
48
0
Order By: Relevance
“…The triplet state dye molecules can undergo one of two photochemical pathways 44 ; quenching by molecular oxygen including the production of singlet oxygen ( 1 O2), or interaction with biomolecules in the vicinity generating radical species. The generated 1 O2 and radical species can initiate multi-site attack on bacteria in the vicinity effecting cell death 55 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The triplet state dye molecules can undergo one of two photochemical pathways 44 ; quenching by molecular oxygen including the production of singlet oxygen ( 1 O2), or interaction with biomolecules in the vicinity generating radical species. The generated 1 O2 and radical species can initiate multi-site attack on bacteria in the vicinity effecting cell death 55 .…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of CV, TBO, and MB dyes is dependent on their concentration, the exposure time, and the intensity of the light source 52,53 . Recent studies from our group have investigated the application of CV, TBO, and MB dyes to polymers to generate antimicrobial surfaces for use in medical devices including tracheal or urinary catheters and tubes for intravenous drips 54,55 . We have shown that the dyes can be readily impregnated into polymers using a swell-encapsulation-shrink process, and the polymers showed potent photobactericidal activity in white light 44,55 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodw as used by Perni et al [43] to incorporate methylene blue/AuNPs into silicone. Later,O zkan et al [44] developed light-activated PDMSt hat contained crystal violet (12)a nd methylene blue (13). These two substances belong to the family of so-called light-activateda ntimicrobial agents( LAAAs).…”
Section: Swell-encapsulation Methodsmentioning
confidence: 99%
“…7 Our research group has developed new ways to potentially reduce HAIs associated with medical devices, by developing new polymeric materials that can be used as catheter materials and to coat hospital surfaces. [8][9][10][11][12][13][14][15][16][17] Such materials include silicone rubber, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 polyvinylchloride, polyurethane and polypropylene. 18 These materials can also be used to treat HAIs caused by commonly touched surfaces in hospital wards (e.g.…”
mentioning
confidence: 99%